Pengaruh Ukuran Perusahaan, Profitabilitas dan Kinerja Lingkungan terhadap Pengungkapan Islamic Social Reporting - Chitra Mutia Syahril (Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to determine the effect of profitability measures and environmental performance on the performance of social reporting companies with financial performance as a moderating variable. Companies listed in the Jakarta Islamic Index (JII) are selected as many as 45 companies with a research period of 5 years from 2016-2020. . The results of this study indicate that company size has no significant effect on Islamic social reporting (ISR). Profitability partially has a significant effect on Islamic social reporting (ISR). Environmental performance partially significant influence on Islamic social reporting (ISR). The size of the company partially has a significant influence on Islamic social with financial performance as moderating. Profitability partially has no significant effect on Islamic social with financial performance as moderating. Environmental performance partially has a significant effect on Islamic social performance with financial performance as a company listed on the Jakarta Islamic Index (JII) for the 2016-2020 period